Necessary nonsense : aesthetics, history, neurology, psychology - Massey, Irving (Cognitive approaches to culture., 2018)
"This book explores the cognitive possibilities of nonsense, literary and philosophical--ranging from Immanuel Kant to Lewis Carol, from examinations of Asperger's Syndrome to the waking state--and demonstrates that there is an element of nonsense, or stage of nonsense, in the normal course of thought"--